2008
DOI: 10.1016/j.juro.2008.06.044
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Open vs Laparoscopic Pediatric Pyeloplasty Using the Pediatric Health Information System Database—Do Benefits of Laparoscopic Approach Recede at Younger Ages?

Abstract: Laparoscopic approach was associated with a shorter hospital stay and decreased parenteral narcotic use in patients older than 10 years. Evolving technique may reveal less morbidity in younger patients. Future comparisons to open pyeloplasty should address specific pediatric age groups and outpatient convalescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
0
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 13 publications
3
48
0
5
Order By: Relevance
“…10 The hospitalization time was identical in both groups (2.5 days), which is comparable and even better than some of the published data with the open or laparoscopic approach. 1,5,7,9 Some recent data showed similar hospitalization time in the open and the laparoscopic group, except with patients over 10 years old in the study by Tanaka and colleagues. 5,9 Ninety percent of patients in our study had a Pippi Salle catheter installed.…”
Section: -7mentioning
confidence: 78%
See 2 more Smart Citations
“…10 The hospitalization time was identical in both groups (2.5 days), which is comparable and even better than some of the published data with the open or laparoscopic approach. 1,5,7,9 Some recent data showed similar hospitalization time in the open and the laparoscopic group, except with patients over 10 years old in the study by Tanaka and colleagues. 5,9 Ninety percent of patients in our study had a Pippi Salle catheter installed.…”
Section: -7mentioning
confidence: 78%
“…1,5,7,9 Some recent data showed similar hospitalization time in the open and the laparoscopic group, except with patients over 10 years old in the study by Tanaka and colleagues. 5,9 Ninety percent of patients in our study had a Pippi Salle catheter installed. This catheter is advantageous in its handling and cost effectiveness; a study by Braga and colleagues found a decrease of $565 (CDN) per patient when they compared externalized pyeloureteral and standard stents and the preclusion of a second general anesthesia with the Salle catheter.…”
Section: -7mentioning
confidence: 78%
See 1 more Smart Citation
“…19 This raises into question the role of additional variables in postoperative opioid administration. Tanaka and colleagues 20 …”
Section: Are the Results Valid?mentioning
confidence: 99%
“…Recently, LP has gradually gained acceptance as a feasible and reliable treatment associated with minimal morbidity in the pediatric population of Western countries since its first report for children in 1995 3 . A recent report obtained from the pediatric health information system in the USA showed that 6.2% of procedures were performed laparoscopically from 2002 to 2007 4 . The main advantage of a laparoscopic approach to UPJO over other minimally invasive alternatives such as endopyelotomy is the ability to replicate each step of the open surgical procedure.…”
mentioning
confidence: 99%